Colonial paradigms of violence : comparative analysis of the Holocaust, genocide, and mass killing - Gordon, Michelle 1980- HerausgeberIn; O'Sullivan, Rachel HerausgeberIn (European Holocaust studies ;, 2022)
In recent years, scholars have rediscovered Hannah Arendt's "boomerang thesis" – the "coming home" of European colonialism as genocide on European soil – as well as Raphael Lemkin`s work around his definition of genocide and the importance of its colonial dimensions. Germany and other European states are increasingly engaging in debates on comparing the Holocaust to other genocides and cases of mass killing, memorialization, "decolonization" and attempts to come to terms with the past ("Vergangenheitsbewältigung").